The Evolving Role of Central Banks. (International Monetary Fund, 1991)
Central Banks should enjoy a fair degree of autonomy in pursuing price stability to promote long-run growth and prosperity. This volume, edited by Patrick Downes and Reza Vaez-Zadeh, contains the papers presented at the fifth IMF seminar on central banking issues in November 1990. The theme was the interdependence of central bank functions and the role of central bank autonomy.